Acute Effects of Short Static, Dynamic, and Contract–Relax with Antagonist Contraction Stretch Modalities on Vertical Jump Height and Flexibility - Clément Cheurlin; Carole Cometti; Jihane Mrabet; Jules Opplert; Nicolas Babault (Sports)
The present study investigated the acute effects of different stretching modalities applied within a warm-up on flexibility and vertical jump height. Thirty-seven young adults participated in four randomized experimental sessions, each corresponding to a different condition: static stretch (SS), dynamic stretch (DS), contract–relax with antagonist contraction (CRAC) or a control condition with no stretch (CTRL). Conditions were five min in total duration, including 2 × 15 s stretches for each muscle group (knee flexor, knee extensor, and plantar flexor muscles). Ten min and five min of cycling preceded and followed these procedures, respectively. Hamstring flexibility and a series of countermovement jump (CMJ) measurements were interspersed within this procedure. Except for CTRL, hamstring flexibility significantly increased (p < 0.01) after all experimental procedures (7.5 ± 6.6%, 4.1 ± 4.9%, and 2.7 ± 6.0% for CRA, SS, and DS, respectively). The relative increase was significantly greater for CRAC as compared CTRL (p < 0.001). Vertical jump height significantly decreased (p < 0.05) immediately after SS (−2.3 ± 3.9%), CTRL (−2.3 ± 3.5%), and CRAC (−3.2 ± 3.3%). Jump height was unchanged after DS (0.4 ± 4.5%). Whatever the condition, no additional jump height alteration was obtained after the re-warm-up. The main findings of the present study revealed that DS is more appropriate for maintaining vertical jump height. However, stretching has no major effect when performed within a warm-up. In contrast, if the main objective is to increase flexibility, CRAC is recommended.